Thinking in an emergency - Scarry, Elaine (New York : W.W. Norton & Co., 2011)
Discusses the global ethics of increased executive power by invoking the idea of an emergency and cites philosophers, neuroscientists, and artists to prove that thinking and taking fast action are compatible.
The seduction to stop thinking -- Four models of emergency thinking. CPR ; Mutual aid contracts ; The Swiss shelter system ; The constituti onal brake on war -- The place of habit in acts of thinking.
Includes bibliographical references (p. 109-141) and index.
Keywords: War and emergency powers; Abuse of administrative power; Emergency management -- Government policy